Sequence, structure and biophysical characterization of CsoR-like hypothetical protein from Geobacillus zalihae strain T1 - Musa, Nasihah; Mangavelu, Ashwaani; Au, Shaw Xian; Mohd Padzil, Azyyati; Kriznik, Alexandre; Mohammad Latif, Muhammad Alif; Jonet, Mohd Anuar; Ahmad Rodzli, Nazahiyah; Leow, Thean Chor; Mohamad Ali, Mohd Shukuri; Raja Abd Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; et al. (Universiti Sains Malaysia, 2024)
Aims: To date, nine classes of copper regulation mechanisms have been discovered in bacteria and CsoR regulator protein is the most recent among them. Only a few have been structurally and functionally characterized. The present study was aimed to isolate and characterize the sequence, structure and biochemical properties of CsoRGz-like hypothetical protein (HP) to be potentially used as a copper sensor protein. Methodology and results: A scan of the complete genome of a Geobacillus zalihae strain T1 revealed the presence of CsoR-like (CsoRGz) HP, which contains CsoR-like_DUF156 domain and highly conserved Cys-His-Cys residues essential for copper binding. It only shares moderate sequence identity with structurally characterized CsoR proteins. CsoRGz-like HP was subjected to sequence analyses to identify important domains, motifs and residues, while circular dichroism and X-ray crystallography were used to determine its secondary and tertiary structures. CsoRGz appears to be a dimer comprising mainly α-helices, with putative, conserved metal-binding ligands, Cys46-His71-Cys75, located on the α2 helix of the protein. Biophysical characterization of CsoRGz using UV/Vis and fluorescence spectrophotometry confirmed its interaction with Cu(I). Docking of Cu(I) to the dimeric structure of CsoRGz showed that Cu(I) could be coordinated by the above metal-binding residues, further stabilized by the hydrophobic core at the metal-binding site. Conclusion, significance and impact of study: The findings in this study suggest that CsoRGz-like HP might be a novel CsoR protein. This adds to the breadth and numbers of possible CsoR proteins, particularly uncharacterized ones, existing in the pool of hypothetical proteins, to be further characterized and compared across bacterial taxa.